Levels of replacing corn by cassava starch on performance and carcass characteristics of bulls finished in feedlot - Moura Dian, Paulo Henrique; do Prado, Ivanor Nunes; Valero, Maribel Velandia; Rotta, Polyana Pizzi; do Prado, Rodolpho Martin; Silva, Roberio Rodrigues; Bertipaglia, Liandra Maria Abaker [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
This work was carried out to study the effects of replacing corn by different levels of cassava starch (0; 12.5; 22.8 and 32.7%) on performance and carcass characteristics of bulls finished in feedlot. Thirty-two crossbred bulls (1/2 Aberdeen Angus vs. 1/2 Nellore) with 18 months old and 380 +/- 24 kg live weight were used in a completely randomized experimental design with four treatments and eight replications. The experiment was realized during 56 days with 14 days for adaptation. The complete diets [roughage (cottonseed hulls) + concentrate (corn, soybean meal and cassava starch)] were given at 8 am and at 4 pm to bulls. It was analyzed the initial weight (IW), final weight (FW), average daily gain (ADG), dry matter intake (DMI), feed conversion (FC), hot carcass dressing (HCD), fat thickness (FAT), Longissimus muscle area (LMA), leg length (LL) and cushion thickness (CT). The IW, FW, ADG, FC, HCW, HCD, FT, LMA, LL and CT did not present difference (P > 0.05) among levels of replacing corn by cassava starch. The results obtained on performance and carcass traits using cassava starch by-products as a replacement for corn can be considered satisfactory.
Keywords: Beef cattle; cassava; cattle performance; cotton hulls; feedlot